Fetal Undernutrition Programming, Sympathetic Nerve Activity, and Arterial Hypertension Development - Mariano, Vinícius Schiavinatto; Boer, Patrícia Aline; Gontijo, José Antônio Rocha (Frontiers in Physiology, 2021)
A wealth of evidence showed that low birth weight is associated with environmental disruption during gestation, triggering embryotic or fetal adaptations and increasing the susceptibility of progeny to non-communicable diseases, including metabolic and cardiovascular diseases, obesity, and arterial hypertension. In addition, dietary disturbance during pregnancy in animal models has highlighted mechanisms that involve the genesis of arterial hypertension, particularly severe maternal low-protein intake (LP). Functional studies demonstrated that maternal low-protein intake leads to the renal decrease of sodium excretion and the dysfunction of the renin-angiotensin-aldosterone system signaling of LP offspring. The antinatriuretic effect is accentuated by a reduced number of nephron units and glomerulosclerosis, which are critical in establishing arterial hypertension phenotype. Also, in this way, studies have shown that the overactivity of the central and peripheral sympathetic nervous system occurs due to reduced sensory (afferent) renal nerve activity. As a result of this reciprocal and abnormal renorenal reflex, there is an enhanced tubule sodium proximal sodium reabsorption, which, at least in part, contributes directly to arterial hypertension development in some of the programmed models. A recent study has observed that significant changes in adrenal medulla secretion could be involved in the pathophysiological process of increasing blood pressure. Thus, this review aims to compile studies that link the central and peripheral sympathetic system activity mechanisms on water and salt handle and blood pressure control in the maternal protein-restricted offspring. Besides, these pathophysiological mechanisms mainly may involve the modulation of neurokinins and catecholamines pathways.